An Analysis of Legal Protection for Consumers in Relation to Predatory Pricing Practices by PT Conch South Kalimantan Cement: A Case Study of Supreme Court Decision No. 951 K/Pdt.Sus-KPPU/2021 - Hana Muthiah; I Made Kantikha; Wasis Susetio; Helvis (GoAcademica Research & Publishing, 2026)
This study analyzes the legal protection afforded to consumers in relation to predatory pricing practices carried out by PT Conch South Kalimantan Cement, as examined in Supreme Court Decision No. 951 K/Pdt.Sus-KPPU/2021. Predatory pricing as an unfair pricing strategy not only disrupts fair business competition but also creates long-term negative effects for consumers, including reduced market choices, the risk of monopolization, and the loss of their rights to fair prices, product quality, and sustainable supply. The research employs a normative juridical method with a case approach, drawing upon judicial decisions, Law No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition, and relevant consumer protection regulations. The findings indicate that PT Conch’s conduct meets the legal criteria for predatory pricing, resulting in adverse impacts on market dynamics and consumer welfare. The Supreme Court’s ruling upholds KPPU’s findings and underscores the role of competition law enforcement as an indirect mechanism for consumer protection. This study concludes that safeguarding consumers from predatory pricing requires not only price monitoring but also consistent enforcement of competition law to ensure a healthy, competitive market structure that supports the fulfillment of consumer rights.